Analysis on grammatical errors using error analysis approach in ESL writing - Antony, Laurien (2022)
Grammatical errors significantly impact the quality of a piece of writing. This study aims to identify the most common types of grammatical errors made in writing by ESL students and to identify the causes of grammatical errors made in writing by ESL students through the study of Error Analysis (EA). It is important to identify the types of errors made to study the prevalence of grammatical errors and see where they can be improved. It is also important to identify the causes of those errors to figure out ways to reduce or eliminate grammatical errors in future writings. The results of this study are analysed through the Error Analysis approach as it is a significantly structured and well-developed approach to study the students’ errors. 20 pieces of essays written by 10 Form Five students were collected and analysed. Each student wrote two essays based on the Malaysian national examination, Sijil Pelajaran Malaysia (SPM) format. According to the findings, the most common type of grammatical errors found in the students’ ESL writing were verb tenses and articles, followed by prepositions, subject-verb agreement, pronouns, tenses, nouns, conjunctions, quantifiers, adjectives, and adverbs in that order. Interviews were conducted to identify the causes of errors. The major causes of grammatical errors made by the students were interlingual and intralingual interference, and other minor causes are assuming the grammar used was correct, overlooking errors and confusion when reading the texts. This study concludes that most of the Form Five students have made various grammatical errors in their ESL writing, and the causes of those errors made by the students were primarily due to their interlingual and intralingual interference.